The Effectiveness of Dental Protection and the Material Arrangement in Custom-Made Mouthguards - Messias, Ana (2021)
Experimental research studies have shown that wearing a mouthguard (MG) is an effective way to prevent tooth or maxillofacial trauma. However, there is a lack of scientific information regarding how the material arrangement within the mouthguard can modify its mechanical response during an impact. Hence, this study aimed to evaluate the influence of material arrangement within custom-made mouthguards on stress transmitted to anterior teeth, bone, and soft tissue after impact. Four 3D finite element models of a human maxilla were reconstructed based on the CBCT of a young patient and analyzed according to the presence or absence of a mouthguard and the type of material arrangement within those with a mouthguard: model NMG with no mouthguard; model CMG representing the conventional arrangement with a single 4 mm-thick ethylene-vinyl acetate (EVA) foil; model FMG presenting layer arrangement with two 1 mm-thick foils of EVA in the outer shell and one 2 mm-thick foil of EVA foam in the core; model HMG presenting a 1 mm-thick compact inner and outer shell of EVA and a 2 mm wide air-filled zone in the core. Linear quasi-static analysis and frontal load were used to simulate an impact with an energy of 4.4 J. Isotropic linear elastic properties were assumed for the bone and teeth but not for the mouthguard protection and oral soft tissues. The results were evaluated and compared in terms of displacement, stretches, and stresses. All the mouthguards analyzed reduced the risk of injury to teeth and bone, reducing the displacement and stress of these structures. However, the implementation of a honeycomb struc-tured layer allowed more significant displacement and deformation of the mouthguard's external layer, thus promoting higher protection of the anatomic structures, namely the root dentin and the bone tissue. Nevertheless, the results also indicate that improving the mouthguard flexibility might increase the soft tissue injuries. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.